Análise dos fatores responsáveis pela alta salinidade do aqüífero fissural da microbacia do Riacho do Feijão - Pedro Avelino/RN - Medeiros, Jailsa da Silva (2006)
The fissures aquifer northeast semi-arid Brazilian, present high text frequently of leave, with of low a hídric availability. The research has as objective main to analyze the components that inside influence in the salinity of the waterbearing fissures of an evaluation physicist-chemistry of the water, leading in consideration the physical interventions of the environment. One used techniques of interpretation of image of Landsat satellite -1999 and delimitation of the micro basin through the topographical map SUDENE. One identified waters of the NaCl type with Ca++ and Mg++ in secondary concentrations. The analyzed wells (15), had presented an average salinity of 5.147 mg/L of STD and a well only supplies drinking waters with 319 mg/L of STD. The recharge of the aquifer one if carries through for infiltration in the open fracture of ortognaisse it migmatization. The type and directions of the fracture do not control the STD. Relations between salinity and out let do not exist. The quality of the well of low salinity is identical the superficial waters (aquifer dam and alluvial). The studies of the meteoric erosion processes had evidenced that in the transformations of the rock in ground, the Ca++ and Na+ are taken for superficial waters. The treatment of the data chemical showed that the grade of Na+, Ca++, Mg++ and Cl-are controlled for the evaporation process, from only water that would have the qualities of superficial waters or the well of low salinity. Already the HCO3-grade is controlled for the precipitation of the dolomite. The STD of this aquifer one would be consequence of the high tax of evaporation of dams constructed in regions of plain topography. You leave them precipitated in deep argillaceous ones dry dams are led for the aquifer in first rains. The research suggests some recommendations for the use and exploitation of the water salinity in piscicultura, carcinicultura, culture of the grass-salt (Atriplex sp), among others